The Effect of Parental Guidance and Emotional Intelligence on Learning Achievement in Social Science - Ahmad Susanto (Journal of Family Sciences, 2019)
The purpose of this study was to determine the effect of parental guidance and emotional intelligence on student learning achievement in social science. The research method was a descriptive survey method. Data collection was done by questionnaires. Data analysis involved descriptive statistical method to find partial and multiple correlation coefficient with ttest. The result showed: 1) there was a significant effect of parental guidance and emotional intelligence together on student learning achievement in social science. Parental guidance and emotional intelligence contributed 64.2% to the student learning achievement in social science; 2) there was a significant effect of parental guidance on student learning achievement in social sciences. This is evidenced by the acquisition of sig= 0.037<0.05 and tcount=2.114; 3) There is a significant effect of emotional intelligence on learning achievement in social sciences. This is evidenced by the p<0.05 and tcount of 6.336.